2017
DOI: 10.3847/1538-4357/aa6573
|View full text |Cite
|
Sign up to set email alerts
|

Early Science with the Large Millimeter Telescope: Detection of Dust Emission in Multiple Images of a Normal Galaxy at z > 4 Lensed by a Frontier Fields Cluster

Abstract: We directly detect dust emission in an optically-detected, multiply-imaged galaxy lensed by the Frontier Fields cluster MACSJ0717.5+3745. We detect two images of the same galaxy at 1.1 mm with the AzTEC camera on the Large Millimeter Telescope leaving no ambiguity in the counterpart identification. This galaxy, MACS0717 Az9, is at z > 4 and the strong lensing model (µ = 7.5) allows us to calculate an intrinsic IR luminosity of 9.7 × 10 10 L and an obscured star formation rate of 14.6 ± 4.5 M /yr. The unobscure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 69 publications
4
23
0
Order By: Relevance
“…We found that deviations towards red UV-slopes with respect to the canonical IRX -β relations are driven by either an ageing stellar population or by varying dust types. Similar values for β and IRX as observed by Capak et al (2015), Bouwens et al (2016), Pope et al (2017), and Smit et al (2017), can be obtained when the stellar emission from a 50-100 Myr old stellar population passes through a screen of dust with a MW attenuation curve. The effect of ageing has been discussed before by many authors (e.g., Kong et al 2004;Grasha et al 2013).…”
Section: Smc Dust In Early Galaxiessupporting
confidence: 68%
See 2 more Smart Citations
“…We found that deviations towards red UV-slopes with respect to the canonical IRX -β relations are driven by either an ageing stellar population or by varying dust types. Similar values for β and IRX as observed by Capak et al (2015), Bouwens et al (2016), Pope et al (2017), and Smit et al (2017), can be obtained when the stellar emission from a 50-100 Myr old stellar population passes through a screen of dust with a MW attenuation curve. The effect of ageing has been discussed before by many authors (e.g., Kong et al 2004;Grasha et al 2013).…”
Section: Smc Dust In Early Galaxiessupporting
confidence: 68%
“…Capak et al (2015), Bouwens et al (2016), Pope et al (2017), and Smit et al (2017) observed a number of highredshift (z > 4) galaxies with a UV-slope β ∼ −1 and IRX∼ 1 or less. These works concluded that these values are consistent with an SMC attenuation curve, suggesting that dust in early Universe galaxies is similar to SMC dust.…”
Section: Smc Dust In Early Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, conversely, interstellar dust may provide protection from the UV background of the intergalactic medium (IGM), which by photoionization heating, could have evaporated dwarf galaxies during the epoch of reionization (Barkana & Loeb 1999). Furthermore, dust obscures as much as half of the light in star-forming galaxies (Lagache et al 2005), and at high redshifts (z3), our understanding of dust-obscured star formation activity in typical star-forming galaxies is very incomplete (e.g., Pope et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such achievement has become feasible only recently thanks to wide-area far-IR/sub-mm surveys conducted by Herschel, ASTE/AzTEC, APEX/LABOCA, JCMT/SCUBA2, and ALMA-SPT (e.g., Gruppioni et al 2013Gruppioni et al , 2015Lapi et al 2011;Weiss et al 2013;Strandet et al 2016;Koprowski et al 2014Koprowski et al , 2016, in many instances eased by gravitational lensing from foreground objects (e.g., Negrello et al 2014Negrello et al , 2017Nayyeri et al 2016). In fact, galaxies endowed with star formation ratesṀ ⋆ a few tens M ⊙ yr −1 at redshift z 2 were largely missed by rest-frame optical/UV surveys because of heavy dust obscuration, difficult to correct for with standard techniques based only on UV spectral data (e.g., Bouwens et al 2016Bouwens et al , 2017Mancuso et al 2016a;Pope et al 2017;Ikarashi et al 2017;Simpson et al 2017). High-resolution, follow-up observations of these galaxies in the far-IR/sub-mm/radio band via ground-based interferometers, such as SMA, VLA, PdBI, and recently ALMA, have revealed star formation to occur in a few collapsing clumps distributed over spatial scales smaller than a few kpcs (see Simpson et al 2015;Ikarashi et al 2015;Straatman et al 2015;Spilker et al 2016;Barro et al 2016;Tadaki et al 2017).…”
Section: Introductionmentioning
confidence: 99%